SISTEM PENGONTROL PLAYSTATION OTOMATIS DENGAN MENGGUNAKAN MIKROKONTROLER ARDUINO UNO PADA MEGA GAME PROBOLINGGO - Purnomo, Teguh; Sujito, Sujito (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
Increased information technology lead to the data processed quickly, precisely, and accurately to produce any information required, as well as in the business world playstation rental. Playing the game is able to sharpen the brain to think, because there are many games available on PlayStation. Starting from the pleasure of the children in the neighborhood of the playstation game, it was established a playstation rental business entity with name mega game. When these tools are used to calculate the time consumption in rental mega playstation games still use the tool manually, by using the TV remote. This causes a loss in the rental mega game because of frequent overtime playstation use the TV remote undetected, causing the user to commit fraud by not paying the excess time.From the results of research conducted can be obtained that the playstation controller automated system using microcontroller arduino uno can provide alternative solutions to the problem and fix the weaknesses of the previous time control systems. Keywords: Control Systems, Microcontroller, Arduino Uno.